STUDY OF LANGUAGE STYLES IN PRESIDENT-ELECT JOE BIDEN’S VICTORY SPEECH - Budi Susatyo; Dholiful Hadi (Prominent, 2022)
This study is a study of the Language Style in a speech on Youtube com with its subtitle,  entitled: President-elect Joe Biden stands on stage with his wife Jill, Saturday, Nov. 7, 2020, in Wilmington, Del. Transcript of President-elect Joe Biden’s victory speech Saturday night in Wilmington, Del., as delivered. Provided by the Biden campaign: The Language Style used by Joe Biden are: Repetition, Metaphor, Euphemism, Persuasion, Climax, Anti-tesis, Repetition, Rhetoric, Idiom, Literal Meaning, Persuasive Slogan.Language Style used by Joe Biden could give a positive comprehension, enthusiasm, motivation, understanding for the effectiveness of the audience as well as the listeners and the viewers. This  can be understood  from his speech that the audience often pay attention in each language style (can be seen on Joe Biden makes a history speech " in Wilmington.Messages can enhance 'understanding' or 'message comprehension'. The use of  Language Style  in Joe Biden speech can facilitate understanding. Complex ideas may be conveyed more clearly through Language Style or rhetoric. Stored messages can help to 'alert' a message. The use of various syntactic patterns or figurative words can help audiences remember an important element in the message. The message conveyed can increase the persuasion appeal. Key words: Figurative Meanings, Speeches, Rhetorics, Motivation, Enthusiasm